1971
DOI: 10.1111/j.1432-1033.1971.tb01597.x
|View full text |Cite
|
Sign up to set email alerts
|

The Regulation of Glyceride Synthesis from Pyruvate in Isolated Fat Cells

Abstract: The incorporation of 14C-labelled pyruvate into glyceride fatty acids and glyceride glycerol has been measured in fat cells prepared from epididymal adipose tissues of normal rats, rats starved for 24 h, rats starved for 24 h and refed a carbohydrate diet for 24 h or rats starved for 24 h and refed a fat diet for 24 h. Rates of fatty acid synthesis were decreased in starved and starved, fat refed cells and increased in starved, carbohydrate refed cells. I n all four dietary states, addition of palmitate to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

1974
1974
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 36 publications
2
38
0
Order By: Relevance
“…Most fructose transport is through GLUT5 that is entirely in the plasma membrane with no modulation of its membrane abundance by insulin [34]. Also the utilization of pyruvate that enters the cells via a monocarboxylate transporter is unaffected by palmitate [1]. (iii) The attenuation by Compound C of the effects of palmitate on glucose utilization, 2-DOG transport and on the palmitate ‘anabolic effect’ as well as its attenuation of the activation of AMPK by palmitate implies that AMPK is a mediator of these effects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most fructose transport is through GLUT5 that is entirely in the plasma membrane with no modulation of its membrane abundance by insulin [34]. Also the utilization of pyruvate that enters the cells via a monocarboxylate transporter is unaffected by palmitate [1]. (iii) The attenuation by Compound C of the effects of palmitate on glucose utilization, 2-DOG transport and on the palmitate ‘anabolic effect’ as well as its attenuation of the activation of AMPK by palmitate implies that AMPK is a mediator of these effects.…”
Section: Resultsmentioning
confidence: 99%
“…The other essential TAG precursor is glycerol 3-phosphate. Adipocytes have minimal expression of glycerol kinase and normally glyceroneogenesis from 3-carbon precursors is low [1]. Therefore cellular glycerol 3-phosphate is largely derived from plasma glucose whose entry into adipocytes is mainly facilitated by the insulin-activated glucose transporter GLUT4.…”
Section: Introductionmentioning
confidence: 99%
“…Early studies in rats showed palmitate to stimulate glucose incorporation into TG fatty acids (10,11). Several studies of high fat feeding in rats and mice, whether or not specifically high in saturated fat, show induction of DNL at a transcriptional or flux level (12)(13)(14)(15).…”
mentioning
confidence: 99%
“…The role of the extraordinarily high mitochondrial phosphoenolpyruvate carboxylase activity in rabbit fat-cells remains unclear at present. The abundance of this activity does not appear to confer any extra ability to carry out 'glyceroneogenesis' (Reshef et al, 1970) since the incorporation of pyruvate or lactate carbon into glyceride glycerol shown in Table 1 was no higher than that found in rat cells (Saggerson & Tomassi, 1971) and was very low compared with the incorporation of glucose into glyceride glycerol.…”
Section: Discussionmentioning
confidence: 99%
“…The procedures for the measurement of the incorporation of '4C-labelled substrates have been described (Saggerson & Tomassi, 1971;Saggerson, 1972a,b). Fat-cell DNA was determined as described by Saggerson (1972a).…”
Section: Fat-cell Techniquesmentioning
confidence: 99%